TRANSFORMASI DIGITAL DALAM PENGELOLAAN SISTEM PENDIDIKAN: PEMANFAATAN INTERACTIVE FLAT PANEL (IFP) DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS 10 DI SMAN 9 GOWA - Dewi IndraSari, Citra; Siti Inganah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of digital technology in the 21st century has driven a transformation in the education system, particularly in the use of interactive learning tools. One of the emerging technologies is the Interactive Flat Panel (IFP), which is able to provide more interactive, collaborative, and student-centered learning. The purpose of this study is to examine the use of IFP in an effort to increase the learning motivation of 10th-grade students at SMAN 9 Gowa. This study applies a descriptive qualitative approach with data collection methods through observation, interviews, learning motivation questionnaires, and documentation. The results showed that before the use of IFP, student learning motivation was relatively low, with only 46% of students showing enthusiasm for learning. After the implementation of IFP, there was a significant increase, namely 78% of students felt more interested, 72% found it easier to understand the material, and 65% were more confident in participating. These findings indicate that the use of IFP can increase students' intrinsic motivation by fulfilling the needs for autonomy, competence, and connectedness, as explained in Self-Determination Theory. This research emphasizes the importance of teacher training and providing adequate digital infrastructure so that IFP is utilized not only as a visual medium, but also as a strategic instrument in supporting educational transformation that is adaptive, innovative, and relevant to the demands of the 21st century.